1)4(х-3)=х+6
4х-12=х+6
4х-х=6+12
3х=18
х=18:3
х=6
2)
4-6(х+2)=3-5х
4-6х+12=3-5х
-6х+5х=3-4
-х=-1
х=1
3)(5х+8)-(8х+14)=9
5х+8-8х-14=9
-3х=9+14-8
-3х=15
3х=-15
х=-15:3
х=-5
4)0,3(8-3у)=3,2-0,8(у-7)
2,4-0,9у=3,2-0,8у+5,6
-0,9у+0,8у=3,2+5,6-2,4
-0,1у=6,2
у=6,2:0,1
у=62
постав 5 звезд
1)4(х-3)=х+6
4х-12=х+6
4х-х=6+12
3х=18
х=18:3
х=6
2)
4-6(х+2)=3-5х
4-6х+12=3-5х
-6х+5х=3-4
-х=-1
х=1
3)(5х+8)-(8х+14)=9
5х+8-8х-14=9
-3х=9+14-8
-3х=15
3х=-15
х=-15:3
х=-5
4)0,3(8-3у)=3,2-0,8(у-7)
2,4-0,9у=3,2-0,8у+5,6
-0,9у+0,8у=3,2+5,6-2,4
-0,1у=6,2
у=6,2:0,1
у=62
постав 5 звезд